155 reputation
9
bio website
location
age
visits member for 2 years, 1 month
seen May 21 at 12:15

Jul
2
awarded  Curious
Apr
14
accepted $\lim_{k\rightarrow \infty}\frac{2^k}{\gamma}\log\mathbb{E}[e^{-\gamma \frac{X}{2^k}}]$
Apr
10
revised $\rho_\gamma(X)=\frac{1}{\gamma} \log \mathbb{E}[e^{-\gamma X}]$
edited title
Apr
10
asked $\lim_{k\rightarrow \infty}\frac{2^k}{\gamma}\log\mathbb{E}[e^{-\gamma \frac{X}{2^k}}]$
Apr
9
accepted $\rho_\gamma(X)=\frac{1}{\gamma} \log \mathbb{E}[e^{-\gamma X}]$
Apr
9
comment $\rho_\gamma(X)=\frac{1}{\gamma} \log \mathbb{E}[e^{-\gamma X}]$
makes sense, thanks for your help and patience
Apr
9
comment $\rho_\gamma(X)=\frac{1}{\gamma} \log \mathbb{E}[e^{-\gamma X}]$
would you please elaborate a bit on the fact that the inequality is strict for all non constant X. ( almost surely ). Thanks in advance!
Apr
9
comment $\rho_\gamma(X)=\frac{1}{\gamma} \log \mathbb{E}[e^{-\gamma X}]$
Thanks! Am I assuming correctly that you used Jensen en.wikipedia.org/wiki/Jensen's_inequality $\frac{1}{\gamma}\log\mathbb{E}[e^{-\gamma 2 X}] \geq \frac{1}{\gamma}\log(\mathbb{E}[e^{-\gamma X}])^2 $
Apr
9
revised $\rho_\gamma(X)=\frac{1}{\gamma} \log \mathbb{E}[e^{-\gamma X}]$
edited tags
Apr
9
asked $\rho_\gamma(X)=\frac{1}{\gamma} \log \mathbb{E}[e^{-\gamma X}]$
Apr
9
awarded  Benefactor
Apr
9
comment $f(z):=\int_{\mathbb{R}} \frac{1}{t-z} d\mu(t)$ show $\lim_{y\rightarrow 0}iyf(iy)=-\mu(\lbrace 0 \rbrace)$
thanks so much!
Apr
9
accepted $f(z):=\int_{\mathbb{R}} \frac{1}{t-z} d\mu(t)$ show $\lim_{y\rightarrow 0}iyf(iy)=-\mu(\lbrace 0 \rbrace)$
Apr
5
awarded  Tumbleweed
Apr
1
awarded  Promoter
Apr
1
comment $f(z):=\int_{\mathbb{R}} \frac{1}{t-z} d\mu(t)$ show $\lim_{y\rightarrow 0}iyf(iy)=-\mu(\lbrace 0 \rbrace)$
Thanks again, but I have one more question. I don't understand the last equality, it is a bit too fast for me to see this. Could you perhaps explain that last step, please?
Mar
29
asked metric makes $\mathcal{C}(\Omega) $ to a complete metric space
Mar
26
asked $f(z):=\int_{\mathbb{R}} \frac{1}{t-z} d\mu(t)$ show $\lim_{y\rightarrow 0}iyf(iy)=-\mu(\lbrace 0 \rbrace)$
Feb
19
asked conversion of number from base 10 to base 16
Feb
13
awarded  Commentator